Comprehensive analysis of water-sediment variation characteristics at the confluence of the upper reaches of the Weigan River and Heizi River with multiple methods and multiple influencing factors. Issue 2 (3rd November 2021) - Zhang, Mingwang; Shi, Kebin
Abstract: In-depth analysis of the characteristics of water and sedimentary changes at the confluence of the upper reaches of Weigan River and Heizi River is the prerequisite and basis for studying the future water and sedimentary situation in the Kizil Reservoir. This article analyzes the trend, mutation point and periodicity of the water and sedimentary sequence with multi-methods. The double cumulative curve method and the attenuation analysis method were used to analyze the impact of precipitation and human activities on runoff and sedimentary transport, and other influencing factors were qualitatively analyzed also. The results showed that: (1) In the past 60 years, Kizil Reservoir's runoff and sedimentary transport have shown an upward trend; the mutation point of the reservoirs' runoff was in 1994; the annual runoff had a periodicity of 7, 13, and 28 years; the annual sedimentary transport had a periodicity of 4, 12, and 26 years. (2) The impact of precipitation and human activities on runoff were 485.37% and −385.37%, respectively; the impact of precipitation on sedimentary transport was first high and then low, while the impact of human activities on sedimentary transport was first low and then high. Solar activities, ENSO, underlying surface changes and glacier snow melt also contributes to water-sediment changes to some extent. HIGHLIGHTS: Various analytical methods were used to analyze the changing trends and mutation points, and comprehensively determined the results. The ensemble empirical mode decomposition (EEMD) method was used to accurately analyze the periodicity of runoff and sedimentary transport. The quantitative and qualitative systematic analysis of the factors which affect water and sedimentary changes were carried out.